The Effect of the Traditional Game-Assisted TGT Model on the Mathematical Knowledge of Fourth Grade Students - Ayu Ardiani; Gusti Ngurah Sastra Agustika; Didith Pramunditya Ambara (Undiksha Press, 2025)
The low competence of student’s mathematical knowledge is influenced by various factors, such as the learning environment, student motivation, interests, intelligence, family support, including teacher strategies in teaching students. To avoid this from happening continuously, an appropriate teaching strategy is needed, one of which is by choosing a learning model that is able to build an effective and enjoyable learning atmosphere. So that a study was conducted that aims to determine the effect of the Team Games Tournament learning model assisted by traditional games on the mathematical knowledge of fourth grade elementary school students. This study is a type of quantitative research with a quasi-experimental design using a non-equivalent control group design. The population in this study was 416 students. The sample selection was carried out using the cluster random sampling technique. The data collection method was the test method. The research instrument was a multiplechoice test. Data on student’s mathematical knowledge competency were analyzed using descriptive statistical analysis techniques and inferential statistics using the Polled Variance t-test. The results of the hypothesis test showed that the Team Games Tournament learning model assisted by traditional games had an effect on the mathematical knowledge of fourth grade students. Based on the results of the research that has been carried out, this model is able to influence student’s mathematical knowledge competency in the material of number patterns and picture patterns. When learning is carried out using this model, students are given the opportunity to become peer tutors, discuss problems to find solutions, and learn in a fun way.